Influence of daily physical activity on fine motor skills of adults around a Fitts task - Louise Robin; Laure Fernandez; Maxime T. Robert; Eric Hermand; Axelle Gelineau; Stéphane Mandigout (Folia Medica, 2023)
Introduction: Achieving our daily tasks depends on the speed-accuracy conflict. Physical activity plays a role in the development of our motor skills. However, the relationship between physical activity level (PAL) and fine motor skills remains largely unexplored. Aim: Our aim was to examine the relationship between the amount of daily physical activity and the performance of healthy adults in a reciprocal aiming task. Materials and methods: Eighty-seven healthy adults completed a reciprocal aiming task using a digital tablet. Four difficulty levels (3-6, determined by target width) and 50 scores for each level were performed using both hands. Movement time, error rate, and performance index were analyzed. PAL was measured using the Global Physical Activity Questionnaire. Spearman correlations and nparLD analysis were used in R Studio to explore the influence of physical activity level, difficulty index on individuals’ performances. Results: Apart from a correlation between PAL and motor performance at the easiest level (r=0.23, p=0.002), there was no correlation between PAL and fine motor performance. Conclusions: The results of our study did not indicate any significant major correlations between daily PAL and fine motor performance except when the constraints of a reciprocal aiming task are the lowest. Further work is needed to consider the use of the reciprocal Fitts task in a clinical setting.